Stability criteria of Aluminum lattice from first-principles - Lin Zhang; Tianle Wang; Feng Liu (Journal of Materials Research and Technology)
The stability of the Aluminum (Al) lattice fundamentally determines the properties of pure Al and its alloys, making it crucial for high-pressure research and alloy development. Through first-principles calculations, we investigated Al lattice behavior under general stress–strain conditions to establish comprehensive stability criteria under large strains. Our analysis revealed three hydrostatic lines representing fcc-Al, bcc-Al, and fct-Al phases under high compressive strain. Within 0-600 GPa, we calibrated two lattice stability criteria with corresponding instability lines, each characterizing a cubic-to-tetragonal transformation. At 110 GPa, bcc-Al transitions from a transitional to a stable phase, which explains the experimental observation of bcc-Al under high-pressure conditions. The relationship between lattice instability and hydrostatic lines generates a novel phase diagram revealing multiple-phase coexistence. These stability criteria govern various structural transformations of fcc-Al, including dislocation, twinning, and stacking faults. This methodological framework provides insights for lattice stability analysis across diverse metallic systems and alloy industries.